The following is a student solution to the inequality

5/12-(x-3)/6≤(x-2)/3

5/12-2/2*(x-3)/6≤4/4*(x-2)/3

5/12-(2x-6)/12≤(4x-8)/12

5-2x-6≤4x-8

-1-2x≤4x-8

-6x≤-9

x≥3/2

There are two mathematical errors in this work. Identify at what step each mathematical error occurred and explain why it is mathematically incorrect.

The first mathematical error occurred going from line ____ to line ____.

Why it is incorrect:


The second mathematical error occurred going from line ____ to line ____.


Why it is incorrect:



Solve the inequality correctly.
Brainliest is correct. Plssss help

Respuesta :

Answer:

Step-by-step explanation:

All of theses "find the error" problems make the assumption that you know how to correctly solve the problem, and that you can compare what you know with what you see.

Here, we have added line numbers so we can be clear about the answers.

line 1: 5/12-(x-3)/6≤(x-2)/3

line 2: 5/12-2/2*(x-3)/6≤4/4*(x-2)/3

line 3: 5/12-(2x-6)/12≤(4x-8)/12

line 4: 5-2x-6≤4x-8

line 5: -1-2x≤4x-8

line 6: -6x≤-9

__

The first mathematical error occurred going from line 3 to line 4.

It is incorrect because the minus sign was not properly distributed. Line 4 should be ...

  5 -2x +6 ≤ 4x -8

__

The second mathematical error occurred going from line 5 to line 6.

It is incorrect because 1 was added on the left and subtracted on the right. The same number needs to be added or subtracted on both sides.

_____

Correct solution:

  5 -2x +6 ≤ 4x -8 . . . . . correct line 4

  11 -2x ≤ 4x -8 . . . . . . . . combine constants

  19 -2x ≤ 4x . . . . . . . . . .add 8

  19 ≤ 6x . . . . . . . . . . . . . add 2x

  19/6 ≤ x . . . . . . . . . . . . . divide by 6